LAND CAPABILITY ANALYSIS OF SOUTH NIAS DISTRICT - Suhenpi Laia; Ihsan Azhari; Cut Nuraini (Bulletin of Engineering Science, Technology and Industry, 2024)
For optimal land use planning, an in-depth analysis of the land to be planned is needed so that the appropriate function can be determined. One of the analyses that needs to be done is the Land Capability Unit (SKL) analysis, which is a structured analysis that considers various physical aspects of the environment in determining land capability. Land Capability Unit (SKL) analysis must be applied in every preparation of a spatial utilization plan so that the utilization plan is not risky for both planning and nature. Land Capability Unit Analysis is carried out using the superimpose/Overlay method which utilizes the ArcGis application. South Nias Regency is a regency area that is divided into many islands with diverse surface morphologies, ranging from very steep to flat surfaces. So in planning land use in South Nias Regency, a structured physical analysis must be carried out so that a land use plan can be determined based on its land capability which is determined based on several aspects considered in the Land Capability Unit analysis process in South Nias Regency. From the results of the analysis that has been carried out, it was found that in South Nias Regency there is land with high capacity covering an area of 44,280.1 Ha or around 17.5 percent and land with very high capacity covering an area of 134,769.8 or around 53.2 percent of the total area of South Nias Regency.